Force uniformity control for large-area roll-to-roll process - Nguyen, Truong Sinh; Lee, Seung Hyun; Kim, Ga Eul; Kwon, Sin; Kim, Kyung Rok; Park, Pyoungwon; Kim, Kwang Young; Kim, Seho; Choi, Young Man; Kim, Kyunghoon (Review of Scientific Instruments, 2021)
Demand for high throughput manufacturing has recently increased in various fields, such as electronics, photonics, optical devices, and energy. Moreover, flexible electronic devices are indispensable in applications such as touch screens, transparent conductive electrodes, transparent film heaters, organic photovoltaics, organic light-emitting diodes, and battery. For these applications, a large-area roll-to-roll (R2R) process is a promising method for producing with high throughput. However, bending deformation of rollers is unavoidable in a large-scale R2R system, which produces non-uniformity in force distribution during processing and reduces the sample quality. In this study, we propose a new R2R imprinting module to mitigate the deformation by using an additional backup roller to achieve uniform force distribution. From numerical simulations, we found that there exists an optimal imprinting force for each backup roller length to obtain the best uniformity. Experimental results using a large-area pressure sensor verified the effectiveness of the proposed method. Finally, the R2R nanoimprint lithography process showed that the proposed method produces patterns of 100 nm width with uniform residual layer thickness, which are distributed across the substrate of 1.2 m width.
Keywords: Film heater; Flexible electronics device; Force distributions; High-throughput; Optical energy; Organic photovoltaics; Roll-to-roll process; Transparent conductive electrodes; Transparent films; Uniformity control